A Suggestion To Solve The Problem Of Asynchronous File Uploads In ASP.NET Without The Need To Use Ajax Technology - Kitab, S. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The file upload is one of the controls of the tool bar of the VisualStodio.NET, but it canâ€™t be used with Ajax technology (It’s almost impossible today to be involved in web application design or development and not be aware of Ajax) because the file upload control donâ€™t support Ajax technology that the execution of the instruction is not completed or the (object is not set) message will appear, although the essential need to use this control with Ajax to gain the asynchronous data transfer that supplied by Ajax, because the file upload donâ€™t work without the Postback operation from the client to the server, and the main idea of Ajax technology is working without Postback operation to the server. After the deep research in www.asp.net and www.msdn.microsoft.com sites the result was that the solution will be in the next version VisualStodio.NET 2008, but it was not a real solution because the Postback operation is continuous. So this paper suggests alternative solution to Ajax by building Web Services to upload files asynchronously and avoid reload the whole web site (Postback operation) when file uploading process is lemented.